Comparison of Chemical Composition and Biological Activities of Eight Selaginella Species - Křížkovská, Bára; Kumar, Rohitesh; Řehořová, Kateřina; Sýkora, David; Dobiasová, Simona; Kučerová, Denisa; Tan, Maria Carmen; Linis, Virgilio; Oyong, Glenn; Ruml, Tomáš; Lipov, Jan; Viktorová, Jitka (Pharmaceuticals (Basel, Switzerland), 2020)
Selaginella P. Beauv. is a group of vascular plants in the family Selaginellaceae Willk., found worldwide and numbering more than 700 species, with some used as foods and medicines. The aim of this paper was to compare methanolic (MeOH) and dichloromethane (DCM) extracts of eight Selaginella species on the basis of their composition and biological activities. Six of these Selaginella species are underinvestigated. Using ultra-high performance liquid chromatography-high-resolution mass spectrometry (UHPLC-HRMS) analysis, we identified a total of 193 compounds among the tested Selaginella species, with flavonoids predominating. MeOH extracts recovered more constituents that were detected, including selaginellins, the occurrence of which is only typical for this plant genus. Of all the tested species, Selaginella apoda contained the highest number of identified selaginellins. The majority of the compounds were identified in S. apoda, the fewest compounds in Selaginella cupressina. All the tested species demonstrated antioxidant activity using oxygen radical absorption capacity (ORAC) assay, which showed that MeOH extracts had higher antioxidant capacity, with the half maximal effective concentration (EC50) ranging from 12 ± 1 (Selaginella myosuroides) to 124 ± 2 (Selaginella cupressina) mg/L. The antioxidant capacity was presumed to be correlated with the content of flavonoids, (neo)lignans, and selaginellins. Inhibition of acetylcholinesterase (AChE) was mostly discerned in DCM extracts and was only exhibited in S. myosuroides, S. cupressina, Selaginella biformis, and S. apoda extracts with the half maximal inhibitory concentration (IC50) in the range of 19 ± 3 to 62 ± 1 mg/L. Substantial cytotoxicity against cancer cell lines was demonstrated by the MeOH extract of S. apoda, where the ratio of the IC50 HEK (human embryonic kidney) to IC50 HepG2 (hepatocellular carcinoma) was 7.9 ± 0.2. MeOH extracts inhibited the production of nitrate oxide and cytokines in a dose-dependent manner. Notably, S. biformis halved the production of NO, tumor necrosis factor (TNF)-α, and interleukin (IL)-6 at the following concentrations: 105 ± 9, 11 ± 1, and 10 ± 1 mg/L, respectively. Our data confirmed that extracts from Selaginella species exhibited cytotoxicity against cancer cell lines and AChE inhibition. The activity observed in S. apoda was the most promising and is worth further exploration.
Keywords: selaginellins; cytotoxicity; anti-inflammatory; flavonoids; Selaginella; AChE inhibition